Transcriptome profiling in response to Kanamycin B reveals its wider non-antibiotic cellular function in Escherichia coli - Chang, Yaowen; Zhang, Xuhui; Murchie, Alastair I. H.; Chen, Dongrong (Frontiers in Microbiology, 2022)
Aminoglycosides are not only antibiotics but also have wider and diverse non-antibiotic cellular functions. To elucidate the understanding of non-antibiotic cellular functions, here we report transcriptome-profiling analysis of E. coli in the absence or presence of 0.5μM and 1μM of Kanamycin B, concentrations that are neither lethal nor inhibit growth, and identified the differentially expressed genes (DEGs) at two given concentrations of Kanamycin B. Functional classification of the DEGs revealed that they were mainly related to microbial metabolism including two-component systems, biofilm formation, oxidative phosphorylation and nitrogen metabolism in diverse environments. We further showed that Kanamycin B and other aminoglycosides can induce reporter gene expression through the 5′ UTR of napF gene or narK gene (both identified as DEG) and Kanamycin B can directly bind to the RNA. The results provide new insights into a better understanding of the wider aminoglycosides cellular function in E. coli rather than its known antibiotics function.